An evaluation of the impact of moving customer service online the e-GSIS experience - Constantino, Vilma M. (University of the Philippines Diliman, 2004)
The main objective of this project is to investigate the development of online services as a new technology that suggests a potential for more efficient and user-centered manner of delivering services in the milieu of Philippine government bureaucracy. Government agencies and institutions have a reputation for slow and sluggish delivery of services, and its customers carry the burden of these inefficiencies. The application of Information and Communications Technology in handling customer services offers a technology-based solution to this problem. Using the e-GSIS-one of the first online services by the Philippine government-as a case study, this project attempts to verify how the transition to public online services will secure a high degree of customer satisfaction. This report presents the results from a survey on members' awareness and usage of the e-GSIS, as well as on the appeal and responsiveness of this new service channel juxtaposed their experiences with traditional offline services, particularly at the frontline. The survey covered members based in Metro Manila, representing 23.4 percent of total membership. Field observations were focused on the frontline services handled by the Customer Relations and Monitoring Department (CRMD) at the main office of the GSIS. Data gathered from the survey were analyzed using descriptive statistical tools and are presented in matrices and graphical representations for a clearer understanding. The frontline service as an offline channel for handling customer service is used as the comparative baseline. During the execution of the survey, GSIS suspended the processing of loan applications as the agency launched a massive updating of its members' records. This event set off a strong negative reaction from its members and the public, thus possibly creating a bias in the responses to the survey. However, secondary information was used to validate key results. The main findings of the study are as follows: Table 1. Main Findings. Area Online Channel (e-GSIS) Awareness and usage. There is a low awareness and usage of the GSIS online service as indicated by the following : 45 percent of 225 respondents do not know about the online service, only 7.5 percent of these respondents have used the e-GSIS at least once; among public school teachers surveyed, only 0.6 percent have accessed the GSIS website; data obtained from the ITSG-GSIS shows that only 1.1 percent of the total GSIS members have registered for an online account as of September 2003; 26 percent of the respondents are unable to use the online service because they have no access to an internet connection; and 80.6 percent of those who have accessed the website used the Internet connection in their office. Appeal and responsiveness. The website features that are important/very important to respondents are : it must provide all the information that they need (85.7 percent); it must be easy to navigate (78.9 percent); information must be accurate and up-to-date (75.3 percent). Since e-GSIS is not fully transactional and respondents' experience with the online service has been few, measures of satisfaction level may be preliminary. However, 59.4 percent of the respondents answered positively when asked if GSIS is providing better service through e-GSIS and 67 percent are willing to recommend it to co-workers/friends. More than half (52.6 percent) of those who have online experience knew about it from friends/co-workers. 53.6 percent used the website to access their personal records while 20.4 percent used it to find out about GSIS programs and policies. Perceived Benefits. Respondents would opt to use the online service because : it saves time (34.3 percent), it is convenient (28.3 percent), it costs less (10.4 percent), it gives better services (15 percent), to avoid the hassles of going to GSIS and dealing with the adversarial attitude of the staff (12 percent). Based on their other studies, online service would bring about the following : more transparency in data, decisions/actions and rules, greater convenience, less corruption since discretion is taken away, cost reduction, improved delivery of services to citizens. Offline Services (Frontline). Quality and responsiveness. Service features rated as satisfactory/very satisfactory are : procedures are easy to follow (82.6 percent); forms are easy to accomplish (85.4 percent); waiting area is pleasant (76.3 percent). Respondents were dissatisfied/very dissatisfied with the following factors : repeat visits needed to complete transaction (48 percent); low responsiveness to their needs (42.5 percent); length of waiting time before being attended to (40 percent). Consequently, 50.7 of respondents' transactions were donw with the assistance of a liaison office because it saves them time and effort. On the other hand, 37.8 percent of the respondents still prefer to use the frontline channel because they can fully explain their needs to the CRO and they believe that personal follow-ups would facilitate the processing of their application. Gap in satisfaction level and importance level. Five areas in the frontline service exhibit a significant gap in how it satisfies customers' needs and how important it is to customers. These areas which need to be addressed are : discourteous attitude of the Customer Relations Officer (CRO), long waiting time, repeat visits needed to complete transaction, low responsiveness to customer needs/complaints, lack of transparency. Service cost from user's end. About 35.4 percent of the respondents missed half-day of work when they personally transacted business at the frontline, while 23 percent skipped work for 1 day. An estimate of lost man-hours resulting from half-day absences of members came up to a minimum of 284,938 man-hours in a year. Expenses incurred when transacting in the GSIS office is P100-P150 for 41 percent of the respondents and less than one hundred pesos for 32.6 percent. Comparatively, 79.4 percent of the respondents who used the online service had zero expenses having used their office's Internet connection to access the site. A closer look at the actual and immediate benefit achieved by transforming a service from offline to online is saving time and gaining flexibility among users. Online service is an improvement because the users can access the service 24/7, instead of only during office opening hours. Since the development of online services is in the early stage, benefits related to process optimization such as faster case handling, higher efficiency and increased user satisfaction are not yet achieved. Furthermore, the take up of moving customer service online depends on both the supply side and the demand side. User awareness of the service, their willingness to use it, ease of use and delivery of benefits through the new facility are important factors in the development of online services. Dissemination of knowledge about the new service channel must be given greater attention as the report reveals very low awareness and usage of the online service. Fundamental process integration (back office) in which the service is re-engineered in moving from offline to online service is also a key to achieving the high efficiency and higher level of service expected from the online facility. In the Philippines, where there is minimal Internet services and which few people can afford, it is expected that the number of members who will use the new technology-based service channel will be few. Public PCs with access to the service and information on other websites would boost the development of online services. In the meantime, service improvements at the frontline customer service, which is commonly used and most preferred by users at this stage, are needed to create integrated services.